Design and Development of an Electric Power Mirror Simulator on Vehicles - Ismail Kholid; Hamid Nasrullah; Syamsul Huda (Jurnal E-Komtek, 2025)
The electric power mirror is one of the essential components in modern vehicles. Understanding how the electric power mirror works is crucial, as it facilitates troubleshooting and repair when the system malfunctions. The development of an electric power mirror simulator aims to help users directly understand the components, working principles, and electrical circuits involved, through an interactive simulator board. This simulator was created using an experimental method involving the design, frame construction, material collection, and testing processes. The test results show that the electric power mirror simulator functions properly and is suitable for use as an educational tool, The average voltage flowing in the circuit is 11.4 volts, and the electric current is 1.48 amperes.